Behavioral Response of African catfish (Clarias gariepinus) to Electrical Flow in an Electrofishing Gear - Azizah, Novia Rahmatul; Nofrizal, Nofrizal; Yani, Alit Hindri (Science, Technology, and Education Care, 2025)
African catfish are a species of fish commonly found in various aquatic environments. Fishermen employ diverse methods to catch fish in seas, rivers, and swamps, utilizing eco-friendly and non-eco-friendly tools. One such tool is electrofishing. Fish behavior is influenced by their ability to adapt to their environment. One observable aspect is the African catfish's swimming patterns and endurance in a research pond. This study was conducted in April 2024 at the Fishing Gear Materials Laboratory, Department of Aquatic Resource Utilization, Faculty of Fisheries and Marine Sciences, Universitas Riau. The research utilized an experimental method, with data collected directly in the Laboratory. African catfish were used as test subjects with a 12-volt electric fishing gear. The results showed that at a treatment distance of 30 cm, the fish required an average of 3,5 seconds to respond to the electric current. The use of electrofishing gear has been proven to cause negative physiological responses, including fainting, external injuries, and mucus release in African catfish, which has implications for the sustainability of the African catfish population. After electrofishing, the condition of the fish showed injuries and fin loss on their bodies, resulting in some fish dying during recovery, although the number of dead fish was fewer than the number of surviving fish